2021
DOI: 10.1101/2021.10.13.464182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allopurinol Blocks Aortic Aneurysm in a Mouse Model of Marfan Syndrome via Reducing Aortic Oxidative Stress

Abstract: The pathogenesis and progression of aortic aneurysm in Marfan syndrome (MFS) involves dysregulated TGF-β and nitric oxide signaling, altered hemodynamics, and biomechanical forces. Increasing evidence indicates that redox stress participates in MFS aortopathy development, though its contribution is not well established. We reported elevated reactive oxygen species (ROS) formation and NADPH oxidase NOX4 upregulation in MFS mice and in patient aortic samples. Here we address the contribution of xanthine dehydrog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
(304 reference statements)
0
2
0
Order By: Relevance
“…ROS-dependent MMP overactivation and SMC apoptosis are established mechanisms of MFS-related TAA formation, that were recently attributed to overexpression of NAPDH oxidase and Xanthine oxidoreductase. 54,6466 Furthermore, ROS were shown to induce endothelial dysfunction 16 and pro-inflammatory NF-κB signaling in MFS. 67 Our data clearly show that MPO constitutes an important mediator of increased aortic ROS formation in MFS.…”
Section: Discussionmentioning
confidence: 99%
“…ROS-dependent MMP overactivation and SMC apoptosis are established mechanisms of MFS-related TAA formation, that were recently attributed to overexpression of NAPDH oxidase and Xanthine oxidoreductase. 54,6466 Furthermore, ROS were shown to induce endothelial dysfunction 16 and pro-inflammatory NF-κB signaling in MFS. 67 Our data clearly show that MPO constitutes an important mediator of increased aortic ROS formation in MFS.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical, molecular and pharmacological studies further implicate xanthine oxidoreductase (XOR) as a source of ROS in the cardiovascular system (Kinugasa et al, 2003;Engberding et al, 2004;Polito et al, 2021). Although the participation of XOR in WBS is unknown, related diseases as Loeys-Dietz and Marfan syndromes showed XOR protein levels increased in aortic samples (Soto et al, 2020;Rodríguez-Rovira et al, 2022). Previous studies have reported that ROS generated by hypoxanthine and xanthine oxidase were inhibited by curcumin (Akter et al, 2020) and the calcium channel blocker verapamil hydrochloride (Liang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%